Implementasi Peretasan Jaringan Menggunakan Alat ESP8266 Dengan Teknik Penetration Testing Metode Deauther Dan Beacon Pada Wireless Tenda F3 - Andrian Fakhrizal; Yudi Kurniawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The internet is very important and has become an important need for people around the world, especially in the current situation. The internet network can be used as a concept where several computers in a university can communicate with each other and can share data and information connected to world connections. Lecturers, employees, and students (users) at one time complained because internet usage was very slow when it was full of users. Due to the excessive use of bandwidth and the lack of proper management of network traffic, it is detrimental to other users. (Prihantoro et al, 2021). YMIK VOCATIONAL SCHOOL had experienced problems with the internet and used the Tenda F3 router and then explained something like the network suddenly dropping and the internet suddenly being slow. According to the statement, the interference was caused by possibly trying to crack the password. From the background description above, the author tries to make a useful research, this hack uses the deauther and beacon methods in hacking wifi networks. The design of this research is based on a microcontroller, the tool used by the author is NodeMCU ESP8266 for hacking targets using Tenda F3. In research methods to obtain data and information, the methods used in the process of collecting data from various sources are observation, interviews and literature studies with the Deauther and Beacon methods, because the use of these methods is for illegal and unethical purposes. However, researchers can provide information about the results of tests that have been carried out related to this method. Research has been conducted using the Deauther and Beacon methods to test the security of Wi-Fi networks. The results show that this method is very effective in hacking Wi-Fi networks that are not encrypted or protected with weak passwords. Deauther attacks can make devices on a Wi-Fi network disconnect from the network, while beacon attacks can make devices connect to fake networks controlled by attackers. The conclusion obtained in this study is that Deauther and Beacon are two techniques used by researchers to carry out hacking attacks on the Tenda F3 Wireless network. Deauther is an attack that utilizes the WiFi protocol feature to force devices to leave the wireless network, while beacon is a technique for creating fake wireless networks that have the same name and configuration as the original wireless network. There are several conclusions and suggestions that can be conveyed by the author as a result of evaluating the development of the system and this final report.